2012
DOI: 10.1002/lary.23379
|View full text |Cite
|
Sign up to set email alerts
|

The association between sleep apnea and young adults with hypertension

Abstract: Objectives/Hypothesis:To study the association between sleep apnea and hypertension in a younger age group than previously studied, adding upper airway sizes at endoscopy as important compounding variables not often included in the past.Study Design:Case control.Methods:We analyzed data on sleep‐disordered breathing (based on polysomnography tests), body mass index (BMI), neck circumference, upper airway endoscopy sizes, and habitus and health history in 120 hypertensive and 120 nonhypertensive participants in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 32 publications
3
12
0
Order By: Relevance
“…Third, due to the limited age distribution in the present study, ranging between 40 and 69 years at baseline, the potential impact of snoring on hypertension in adults younger than 40 years old could not be assessed. To date, only a few studies investigated whether SDB increases risk for hypertension in a young‐adult population, and results are extremely controversial (Asha'ari, Hasmoni, Ab Rahman, Yusof, & Ahmad, ; Pensuksan et al, ). Last, the diagnosis of hypertension was based on BP measurements from a single visit.…”
Section: Discussionmentioning
confidence: 99%
“…Third, due to the limited age distribution in the present study, ranging between 40 and 69 years at baseline, the potential impact of snoring on hypertension in adults younger than 40 years old could not be assessed. To date, only a few studies investigated whether SDB increases risk for hypertension in a young‐adult population, and results are extremely controversial (Asha'ari, Hasmoni, Ab Rahman, Yusof, & Ahmad, ; Pensuksan et al, ). Last, the diagnosis of hypertension was based on BP measurements from a single visit.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, short sleep duration was found to be a risk factor in American population [8], while the significant association was not reported in Chinese population [10]. In terms of sleep apnea, positive association (OR = 1.72, AHI ≥ 30) was found in Malaysian young adults [11], there is, however, no significant results were found in French population [12]. Recent data on the effects of sleep status on hypertension should be explored.…”
Section: Introductionmentioning
confidence: 93%
“…Both Pan et al [ 18 ], in their study on alcohol consumption, chronic diseases and sleep apnea, and hypertension, and Wang et al [ 20 ], in their study on the prevalence of hypertension and circadian blood pressure variations in Chinese patients, found hypertension to be significantly associated with sleep apnea. Asha'ari et al also identified this significant association in a young (mean age of 27) population [ 21 ]. Sleep apnea has been associated with congestive heart failure [ 7 , 9 , 50 , 51 ] and myocardial infarction [ 7 , 52 ], but as “heart disease” in the SARR data was not defined, it is difficult to discuss this finding.…”
Section: Discussionmentioning
confidence: 91%
“…Hypertension has been identified as a risk factor for sleep apnea in numerous studies [ 16 18 , 20 , 21 ]. Luyster et al identified a significantly higher cardiovascular risk (BMI ≥ 30 kg/m 2 , sedentary lifestyle, hypertension, and diabetes) in the group with sleep apnea alone [ 16 ].…”
Section: Discussionmentioning
confidence: 99%